Sistema de producción de cuyes y su influencia en la mejora de los ingresos económicos de las familias productoras de la Asociación El Cuyazo de Conache - Laredo - Paredes Gallardo, Luis Miguel (2016)
The present study aims to determine the influence of production systems guinea pigs in the economic income of producer families of the Cuyazo Conache Association of Laredo district, where the next problem is suggested: How does a production systems guinea pigs influences in improving the economic income of producer families of the Cuyazo Conache Association – Laredo district?, for which the following hypothesis was raise: “The production systems guinea pigs influences improving economic income or producer families of Cuyazo Conache Association”. The research methodology used was type: applied, not experimental and transeccional, inductive – deductive method, hypothetical – deductive method, analysis – synthesis method and the hermeneutical method, with a correlational/causal design was used, direct observation, and the survey also used as a techniques for research. According to the results we can say that a production systems guinea pigs significantly influences the economic income of producer families, as evidenced by the present study, where 45% of respondents receive living wage and 64% have capacity savings and that the results produced by the production, allowing them to contribute to the economic needs of the family. By the results presented in this research, it has proposed a model in guinea pigs production cost for commercial production system, allowing them to get guinea pigs at a lower cost and good weight an early age.